KARAKTERISTIK STRUKTUR MIKRO ORGAN LAMUN Enhalus acoroides MENGGUNAKAN TEKNIK SEM (Scanning Electron Microscope) - NATSIR, NUR ALIM (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Seagrass is an aquatic iota that is capable of accumulating pollutants such as heavy metals dissolved in water. The waters of Marlosso and Nametek along the waters of Kayeli Bay are currently polluted due to illegal gold mining activities that use mercury (Hg) and anthropogenic activities that produce lead (Pb) pollutants that pollute these waters. Mercury (Hg) is a type of heavy metal BIII (toxic and dangerous material) which is toxic to all living things, either in its single form (metal) or in its compounds. While lead (Pb) is a heavy metal produced by human activities around the waters such as household and transportation waste. These pollutants can enter the waters with the help of rainwater. Heavy metal BIII that accumulates in waters can affect the organisms in it such as the morphology of seagrass organs. Identification of the morphological structure of the seagrass Enhalus acoroides using the SEM (Scanning Electron Microscope) method with a magnification of 2000x. The research was carried out at the Laboratory of Minerals and Advanced Materials, State University of Malang, on June 24-August 24, 2021 and sampling in Marlosso and Nametek waters, Buru Regency, Maluku. The results showed that all seagrass organs had undergone morphological changes in the arrangement of irregular root fibers as well as rhizomes and leaves that experienced thickening of the epidermal cell walls as a form of adaptation to heavy metal absorption. Keywords: Seagrass, Morphology, Heavy metal, SEM